Online scrutiny of people with nice cars: A comparative analysis of Chinese, Russian, and Anglo-American outrage. Issue 3 (September 2020) - Huang, Qian; Gabdulhakov, Rashid; Trottier, Daniel
Connected by platforms and equipped with mobile recording devices, social media users are able to conduct near-constant mutual scrutiny. Such mediated scrutiny sometimes escalates to public denunciations online and even mediated or embodied interventions. A recurring theme of such scrutiny can be observed not only on Chinese social media but also on platforms in Russia and elsewhere, in which hostility is openly expressed towards people with nice cars (i.e. late model, luxury, foreign vehicles). In these cases, nice cars are not merely a fact provided by participants in their denunciations; they also serve as an implication of the privileges the owners might possess. By juxtaposing cases in China against other socio-political contexts, the research intends to achieve a better understanding of how and why nice cars are rendered meaningful by participants via mediated scrutiny on social media in China and beyond. The research collects and analyses relevant social media discourses on platforms including Sina Weibo (China), YouTube (Russia), and Facebook (United Kingdom; Australia; United States). Comparing and contrasting cases in different countries, the research demonstrates various forms of critical and populist sentiments that are shaped by unique socio-cultural and political contexts.